Quality of life assessment by WHOQOL-BREF in panic disorder patients during treatment (Archives of Clinical Psychiatry, 2008)
BACKGROUND: Panic disorder (PD) patients show more physical and psychological impairment, than the general population. OBJECTIVES: Our aims are to compare quality of life between PD patients during treatment and healthy subjects and to associate social, demographic and clinical factors with quality of life scores. METHODS: It is a cross-sectional study with 20 PD patients and 20 healthy controls. Anxiety levels assessment: Beck Anxiety Inventory, Hamilton Anxiety Rating Scale, STAIT - Form Y. Panic severity; Panic Agoraphobia Scale; social and environmental problems and global assessment functioning (Axis IV and V, DSM-IV-TR) and quality of life by WHOQOL-BREF. RESULTS: PD patients were 65% female. Mean age = 37.55 ± 9.06. Quality of life domain scores: physical = 57.86 ± 17.56; psychological = 56.04 ± 18.31; social = 56.25 ± 25.92; and environmental = 47.03 ± 16.92; smokers = 20%; BAI = 23.40 ± 15; STAI-S= 43.50 ± 8.79; STAI-T = 50.10 ± 9.19; PAS = 13.60 ± 9.40. DISCUSSION: No significant differences were observed between groups about gender, age, schooling, religion, marital status nor individual income, but family income was significantly higher among controls. All domains of quality of life are significantly impaired among PD patients, compared to healthy controls. Panic disorder compromises well being. Psychosocial problems and high levels of anxiety can also negatively impact quality of life of PD patients.